A bivalent virus-like particle based vaccine induces a balanced antibody response against both enterovirus 71 and norovirus in mice. Issue 43 (26th October 2015) - Wang, Xiaoli; Ku, Zhiqiang; Dai, Wenlong; Chen, Tan; Ye, Xiaohua; Zhang, Chao; Zhang, Yingyi; Liu, Qingwei; Jin, Xia; Huang, Zhong
Highlights: A combination vaccine comprising EV71- and NoV GII.4-VLPs was formulated. The bivalent vaccine elicited a balanced antibody response toward both EV71 and GII.4. The bivalent vaccine-induced antibodies exhibited inhibitory effects on EV71 and NoV GII.4. Abstract: Noroviruses are the main cause of severe viral gastroenteritis, which results in estimated 200, 000 deaths each year, primarily in children in the developing world. Genogroup II.4 (GII.4) strains are responsible for the majority of norovirus outbreaks. Enterovirus 71 (EV71), the leading causative agent of hand, foot and mouth disease, has recently been prevalent in Asia-Pacific regions, resulting in significant morbidity and mortality in young children. However, no vaccine is commercially available for either norovirus GII.4 or EV71. Recombinant virus-like particles (VLPs) derived from either GII.4 or EV71 have been shown to be promising monovalent vaccine candidates. In this study, we investigate the possibility to formulate a VLP-based bivalent vaccine for both norovirus GII.4 and EV71. The GII.4- and EV71-VLPs were produced in a baculovirus-insect cell expression system. A bivalent combination vaccine comprised of GII.4 and EV71 VLPs was formulated and compared with monovalent GII.4- and EV71-VLPs for their immunogenicity in mice. We found that the bivalent vaccine elicited durable antibody responses toward both GII.4 and EV71, and the antibody titers were comparable to that induced by the monovalent vaccines, indicating there is no immunological interference between the two antigens in the combination vaccine. More significantly, the bivalent vaccine-immunized mouse sera could efficiently neutralize EV71 infection and block GII.4-VLP binding to mucin. Together, our results demonstrate that the experimental combination vaccine comprised of GII.4 and EV71-VLPs is able to induce a balanced protective antibody response, and therefore strongly support further preclinical and clinical development of such a bivalent VLP vaccine targeting both norovirus GII.4 and EV71.